Time to maternal death and its predictors among obstetric ICU patients in a resource-limited setting: A 10-year survival analysis - Tigist Nega Alemu; Wondimagegn Genaneh Shiferaw; Workneh Elias Orsongo; Solomon Medina Megule; Wondu Feyisa Balcha (PLoS ONE, 2026)
Background Maternal mortality remains a major concern in resource-limited settings, particularly among critically ill obstetric patients requiring intensive care unit (ICU) admission. Objective To assess the time to maternal death and identify its predictors among obstetric patients admitted to the intensive care unit (ICU) in a resource-limited tertiary hospital in southern Ethiopia, over a ten-year period. Methods A retrospective cohort study was conducted among 378 obstetric patients admitted to the ICU between 2014 and 2023. Kaplan-Meier analysis estimated survival probability, multivariable Cox proportional hazards regression identified independent predictors of time to maternal death reported as adjusted hazard ratios (AHR) with 95% confidence intervals, and a Fine-Gray competing-risks model was additionally conducted with discharge alive as the competing event. Results Of 378 obstetric ICU admissions, 126 resulted in maternal death, with a median time to death of 2.71 days (95% CI: 2.13–3.44); 71.4% of deaths occurred within the first five days, and survival probability declined rapidly before stabilizing after ten days. Rural residency (AHR 1.56, 95% CI 1.03–2.37), shock (AHR 2.27, 95% CI 1.44–3.56), multi-organ failure (AHR 1.75, 95% CI 1.09–2.78), mechanical ventilation (AHR 1.82, 95% CI 1.11–2.98), and impaired consciousness (moderate GCS: AHR 2.94; severe GCS: AHR 5.43, both p < 0.001) were independently associated with higher hazard of death, with findings consistent across the Fine–Gray competing-risks model. Conclusion Maternal ICU deaths occurred early, with most fatalities within the first week of admission and survival probability declining sharply in the first ten days. Shock, multi-organ failure, invasive mechanical ventilation, impaired consciousness at admission, and rural residency were independent predictors of shortened time to maternal death. Interventions targeting these conditions must be initiated early and urgently, particularly within the critical first days of ICU admission, to improve survival in resource-limited settings.